2012
DOI: 10.3389/fgene.2012.00244
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial deficiency: a double-edged sword for aging and neurodegeneration

Abstract: For decades, aging was considered the inevitable result of the accumulation of damaged macromolecules due to environmental factors and intrinsic processes. Our current knowledge clearly supports that aging is a complex biological process influenced by multiple evolutionary conserved molecular pathways. With the advanced age, loss of cellular homeostasis severely affects the structure and function of various tissues, especially those highly sensitive to stressful conditions like the central nervous system. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 130 publications
1
24
0
Order By: Relevance
“…Serine-threonine protein kinase Glycogen syntase kinase 3 beta (GSK3-beta) encoded by the gene sgg ( (2011), Troulinaki and Bano (2012). Genes (proteins) involved in life span control are in red (for references, see Inoki and Guan 2006).…”
Section: Glycogen Syntase Kinase 3 Betamentioning
confidence: 99%
“…Serine-threonine protein kinase Glycogen syntase kinase 3 beta (GSK3-beta) encoded by the gene sgg ( (2011), Troulinaki and Bano (2012). Genes (proteins) involved in life span control are in red (for references, see Inoki and Guan 2006).…”
Section: Glycogen Syntase Kinase 3 Betamentioning
confidence: 99%
“…Intriguingly, protein misfolding, whether it is mediated (Morley et al, 2002;van Ham et al, 2010) or not (David et al, 2010) by polyglutamine repeats, increases with age. This suggests that protein aggregation is inherent with age and is not restricted to a subset of proteins that have been implicated in diseases like neurodegeneration (David et al, 2010).…”
Section: The Effects Of Neuronal Stress-sensing Pathways On Lifespan mentioning
confidence: 99%
“…Similarly, mitochondrial dysfunction has been implicated in neurodegenerative diseases (reviewed in Eckert et al, 2011;Reddy and Reddy, 2011;Swerdlow, 2011;Troulinaki and Bano, 2012;Yin et al, 2012), although it remains unclear whether the functional changes seen in the healthily aging brain are distinct Frontiers in Genetics | Genetics of Aging from the pathological processes associated with neurodegenerative diseases. The empirical evidence at hand today thus suggests that neuronal mitochondria play an important role in maintaining organismal homeostasis and in influencing aging.…”
Section: The Role Of Mitochondria In Brain Aging and Longevitymentioning
confidence: 99%
See 1 more Smart Citation
“…TORC1 signaling transactivates/represses PH4-4 that induces pro-survival factors expression for life extension under nutrient restriction [85]. Moreover, TORC1 can increase protein synthesis and extends lifespan by both activating the ribosomal subunit S6 kinase (S6K) and inhibiting 4E-BP1 (a negative regulator of translation) [81, 97]. Meanwhile, investigations in C. elegans as well as other organisms have shown that autophagy is induced by inhibition of TORC1 [46].…”
Section: Introductionmentioning
confidence: 99%